2022
DOI: 10.3390/su14042247
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Production of Stiff and Crystalline Bacterial Cellulose from Orange Peel Extract

Abstract: In this work, a potentially economic and environmentally friendly method for the synthesis of bacterial cellulose (BC) by Gluconacetobacter xylinus from a biomass containing orange peel extract was evaluated. Orange peel extract was used as a culture medium without any hydrolysis treatment, thus speeding up the synthesis procedure. The efficacy of orange peel as a carbon source was compared with that of sucrose. The orange peel extract formed thicker cellulose gels than those formed using sucrose. X-ray diffra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 42 publications
(48 reference statements)
1
4
0
Order By: Relevance
“…The average diameter of nanocrystals was 17-29 nm. These results are in line with numerous studies (Ahmed et al, 2023;Padmanabhan et al, 2022). EDS analysis was performed to detect and confirm the presence of the traces of mineral ions and elements present in the structure of bacterial cellulose.…”
Section: Fig 6 Eds Image Of Bacterial Cellulose From Iraqi Vinegar's ...supporting
confidence: 88%
“…The average diameter of nanocrystals was 17-29 nm. These results are in line with numerous studies (Ahmed et al, 2023;Padmanabhan et al, 2022). EDS analysis was performed to detect and confirm the presence of the traces of mineral ions and elements present in the structure of bacterial cellulose.…”
Section: Fig 6 Eds Image Of Bacterial Cellulose From Iraqi Vinegar's ...supporting
confidence: 88%
“…Güzel and Akpınar [ 33 ] reported that kiwi fruit peel hydrolysate was the higher for bacterial cellulose by Komagataeibacter hansenii GA2016 among other fruit peels. Padmanabhan, Lionetto, Nisi, Stoppa and Licciulli [ 34 ] produced crystalline bacterial cellulose by Gluconacetobacter xylinus using orange peel extract as a substrate. Likewise, orange peel extract was used for bacterial cellulose production by K. sucrofermentans DSM 15973.…”
Section: Resultsmentioning
confidence: 99%
“…In Figure 1 , the XRD pattern of pristine BC and synthesized CMC powders were reported. The crystalline peaks corresponding to cellulose I (2q 14.4 (101), 16.6 (101), and 22.6 (002)) were present in the BC sample [ 20 ]. The XRD patterns of CMC samples showed a decrease in crystallinity when the reaction time of BC in NaOH solution increases, caused by the separation of hydrogen bonds in cellulose [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…BC pellicles were obtained by the fermentation process of the sweetened black tea with Gluconacetobacter xilinus strains, as reported in our previous work [ 20 ]. The culture medium was prepared by adding sucrose and tea bags to boiling water (1 L).…”
Section: Methodsmentioning
confidence: 99%